A new ASAP Scoring System and Risk Table to predict second prostate biopsy outcomes - Ediz Caner; Akan Serkan; Kaya Neslihan; Ihvan Aysenur (Archives of Medical Science)
Introduction This study aimed to discuss the necessity of a second prostate biopsy in patients with atypical small acinar proliferation (ASAP) and to develop a scoring system and risk table to be used as new criteria for a second biopsy.